Химические превращения в системе OsO₄—S₂Cl₂—Se—KCN—4-CNPy - Янко, О.Г. (Украинский химический журнал, 2013)
Рассмотрены химические превращения в системе OsO₄—S₂Cl₂—Se—KCN—4-CNPy и получены родственные комплексные соединения — тиоселенохлориды составов Os₂S₆Se₂Cl₈(I) и Os₄S₁₁SeCl₈ (II), из которых методами цианирования синтезированы цианопроизводные Os₂S₂Cl₄(4-CNPy)₄ (III) и K₆Os₂S₂O₆(CN)₈ (IV) соответственно. Комплекс I является “прекурсором”, формирующим общий для всех соединений ряда кластерный остов [Os(μ-S)₂Os]. Химические взаимодействия рассмотрены с учетом состава реакционной среды и донорных свойств лигандов, усиливающихся в ряду S < 4-CNPy < Cl < CN. Вивчено хімічні перетворення у системі OsO₄—S₂Cl₂—Se—KCN—4-CNPy та одержано споріднені комплексні сполуки — тіоселенохлориди складів Os₂S₆Se₂Cl₈(I) та Os₄S₁₁SeCl₈ (II), з яких методами ціанування синтезовано ціанопохідні Os₂S₂Cl₄(4-CNPy)₄ (III) та K₆Os₂S₂O₆(CN)₈ (IV) відповідно. Комплекс I є “прекурсором”, який формує загальний для всіх сполук ряду кластерний остов [Os(μ-S)₂Os]. Хімічні взаємодії розглянуто з урахуванням складу реакційного середовища та донорних властивостей лігандів, що посилюються у ряду S<4-CNPy<Cl<CN. The paper considers chemical transformations in the system OsO₄—S₂Cl₂—Se—KCN—4-CNPy, were a number of related complex compounds: thioselenochlorides of the compositions Os₂S₆Se₂Cl₈(I) and Os₄S₁₁SeCl₈ (II) have been obtained, and the cyano derivatives Os₂S₂Cl₄(4-CNPy)₄ (III) and K₆Os₂S₂O₆(CN)₈ (IV), respectively, have been obtained from them by cyanation methods. The complex I is a "precursor" which forms a cluster skeleton [Os(μ-S)₂Os], which is common to all compounds of the series. Chemical interactions have been considered with allowance for the composition of the reaction medium and the donor properties of ligands, which are enhanced in the order S<4-CNPy<Cl<CN.